SISTEM INFORMASI MANAJEMEN PEGAWAI BERBASIS WEB KEJAKSAAN TINGGI KALIMANTAN TENGAH - Christina, Sherly; Licantik, Licantik; Suganda, Nor Aliya (Universitas Palangka Raya, 2015)
High Prosecutor General of Central Kalimantan is an agency engaged in law in the province ofCentral Kalimantan. In the High High Prosecutor General of Central Kalimantan, the management ofemployment data is still done manually. Therefore, the High Prosecutor General of Central Kalimantan,especially on the staffing needs an application programs that can perform the data of personnelmanagement by computerizedPersonnel Management Information System (SIMPEG) is an application that is intended toperform the data of personnel management with user friendly design. Personnel Management InformationSystem was created using descriptive research method with case study at the High Prosecutor General ofCentral Kalimantan. Where the data collection techniques used include observation, interviews, andstudies liberatur. The analysis and design methods used in the manufacture of the system as a modelprocess using DFD and ERD as a data model. In developing the application, this website using the PHPprogramming, MySQL database and a classical application cycle method called waterfall with 5 (five)stages. It is include Analysis, Design, Coding, Testing and Maintenance.By the program of Personnel Management Information System which the application isconcerned with the activities of processing employee data can be maintained, because this applicationprogram is a simplification of the forms of documents or manually archiving media and equipped with apassword, the need to improve the control and data security is guaranteed because not all people havethe right to access the data or change the data.